To be continued? Book review of ‘Nuclear arms control in Russian-American strategic relations (2010 — early 2020s)’ by O.M. Aleksandriya and A.G. Savel’ev - V. I. Mizin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The book under review is a new monograph by O.M. Aleksandriya and A.G. Savel’ev ‘Nuclear arms control in Russian-American strategic relations (2010 — early 2020s)’ published in 2024. The reviewer notes the academic novelty of the study as the authors examine issues of nuclear arms control in the relations between the United States and the Russian Federation within a broader historical, international and military-technological framework. The reviewer considers the content of the book’s three chapters and the authors’ key findings regarding such controversial issues, as the ongoing impasse in the strategic dialogue and the possible role of both third countries and new types of weapons in the negotiations on nuclear arms control, whenever they resume. The reviewer agrees with the authors that in a current situation a limited modernization of the New START provisions with their limits and verification measures is the most viable option, given the lack of feasible opportunities for qualitative development and deepening of the dialogue on nuclear arms control and its adaptation to new strategic realities. At the same time, the reviewer notes that the book lacks a detailed analysis of changes in the Russian-American strategic nuclear balance over the last fifteen years. Meanwhile, this balance has changed significantly, which will be crucial for the Russian-American strategic dialogue when (if) it resumes. This remark, however, by no means downplays the merits of the presented research and only indicates the prospects for its further development. As such, this monograph is a timely and insightful research that would be of interest to both specialists and anyone concerned with the issues of international security, arms control and Russian-American relations.